2015
DOI: 10.1016/j.ihj.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention in a rare variety of single coronary artery

Abstract: We present a case of 50-year-old male having unstable angina. A rare type of single coronary artery was identified during the Coronary angiogram. The left anterior descending (LAD) and left circumflex artery (LCX) had originated from the proximal segment of right coronary artery along with significant lesion in LCX. Computed tomographic (CT) coronary angiogram confirmed the origin and course following which successful percutaneous coronary intervention (PCI) was done to LCX. The incidence of this type of coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…CT angiography might be very useful in detecting the anatomical malformations, acute angle take-off, the transmural course, and compression between the great arteries, which would require surgery. 4 Canbay et al 5 reported three cases of anomalous single coronary artery detected incidentally during routine coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…CT angiography might be very useful in detecting the anatomical malformations, acute angle take-off, the transmural course, and compression between the great arteries, which would require surgery. 4 Canbay et al 5 reported three cases of anomalous single coronary artery detected incidentally during routine coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…3 Anomalous origin of LAD localized at the right coronary ostium, at RCA itself, and pulmonary artery have been reported. 4,5 In these cases inability to selectively cannulate coronary arteries or even mistakenly deemed to be absent, may lead to catastrophic outcomes at the time of acute myocardial infarction.…”
mentioning
confidence: 99%